2021
DOI: 10.1155/2021/5547635
|View full text |Cite|
|
Sign up to set email alerts
|

miR-183-5p Is a Potential Molecular Marker of Systemic Lupus Erythematosus

Abstract: Objective. To investigate microRNA (miRNA) expression profiles in individuals with systemic lupus erythematosus (SLE) and identify the valuable miRNA biomarkers in diagnosing and monitoring SLE. Methods. Next-generation sequencing (NGS) was performed to assess miRNA amounts in peripheral blood mononuclear cells (PBMCs) from four SLE cases and four healthy controls. Quantitative polymerase chain reaction (qPCR) was carried out for validating candidate miRNAs in 32 SLE cases and 32 healthy controls. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A single-center study found that exosomal miR-146a expression was significantly downregulated and negatively correlated with anti-dsDNA antibody levels and ESR in SLE patients; Conversely, miR-21 and miR-155 were significantly elevated and positively correlated with proteinuria, which indicated that they may serve as potential biomarkers for the development of LN (95). The level of miR-183-5p expression in the PBMCs of SLE patients was positively correlated with SLEDAI-2000 and the amount of anti-dsDNA antibody by negatively regulating transcription factor (Foxo1) expression, which can be used as SLE biomarkers (96). Also, several miRNAs (miR-485-5p, miR-132, miR-145, and miR-183) have been suggested as promising SLE biomarkers (97)(98)(99).…”
Section: Exosome-derived Mirna and Its Function In Slementioning
confidence: 97%
“…A single-center study found that exosomal miR-146a expression was significantly downregulated and negatively correlated with anti-dsDNA antibody levels and ESR in SLE patients; Conversely, miR-21 and miR-155 were significantly elevated and positively correlated with proteinuria, which indicated that they may serve as potential biomarkers for the development of LN (95). The level of miR-183-5p expression in the PBMCs of SLE patients was positively correlated with SLEDAI-2000 and the amount of anti-dsDNA antibody by negatively regulating transcription factor (Foxo1) expression, which can be used as SLE biomarkers (96). Also, several miRNAs (miR-485-5p, miR-132, miR-145, and miR-183) have been suggested as promising SLE biomarkers (97)(98)(99).…”
Section: Exosome-derived Mirna and Its Function In Slementioning
confidence: 97%
“…The expression of miR-146a, miR-155, miR-371b-5p, and miR-5100 is increased in the peripheral blood of SLE patients (65, 66). The expression level of miR-183-5p is positively correlated with SLEDAI scores and the amount of anti-dsDNA antibodies (67). Serum hsa-miR-766-3p regulates the PI3K-AKT-mTOR pathway in SLE patients and participates in kidney injury (68).…”
Section: Mirnas As Sle Biomarkersmentioning
confidence: 99%
“…[1][2][3] Although the underling molecular mechanisms of SLE are still not fully clarified, the autologous nucleic acids are attacked by immune responses in SLE patients resulting from multiple genetic and environmental factors. 4,5 Meanwhile, the accumulation of overproduced autoantibodies would lead to the injury of various organs, such as kidney, skin, heart, and lungs. 6 Accordingly, the mortality rate of SLE patients is almost three times higher than healthy individuals, and the rate will increase as the disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a complex chronic, inflammatory systemic autoimmune disease involving innate and adaptive immune responses, usually characterized by flare, variable course, and multiple organ dysfunction 1–3 . Although the underling molecular mechanisms of SLE are still not fully clarified, the autologous nucleic acids are attacked by immune responses in SLE patients resulting from multiple genetic and environmental factors 4,5 . Meanwhile, the accumulation of overproduced autoantibodies would lead to the injury of various organs, such as kidney, skin, heart, and lungs 6 .…”
Section: Introductionmentioning
confidence: 99%